Hubungan Antara Persepsi Terhadap Kompensasi Dengan Disiplin Kerja Awak Bus Po Akas Probolinggo - M. Wimbo Wiyono (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2011)
As a provider of transportation services, good human resource management became one of the efforts to support the strength of human resources available in the company. Human resources is also spearheading the company's progress in services mangingat nature of the business. Security, safety and convenience services to the passengers or users of bus services is preferred. One way to improve the quality of service to passengers or users of bus services needed to boost labor discipline on operational officer. There was a positive relationship between perceptions of compensation by the bus crew Akas work discipline. The more positive employee perceptions of compensation, the higher the employee discipline. Conversely, the negative employee perceptions of compensation will get low employee discipline. Perceptions of compensation subject showed a high category of temporary work discipline at the time of research subjects are also in high positions. Effective contribution to the perception variable compensation on employee discipline by 25.7% while 74.3% are influenced by other factors not addressed in this study.